ANALISIS HUBUNGAN ANTARA DURASI PENGGUNAAN GADGET TERHADAP TINGKAT KEPARAHAN MIOPIA - Aulia, Zidni Rahma; Septia Habiba, Putri Ghanim; Nugraha, Opep Cahya; Simarmata, Murni Marlina (Jurnal Mata Optik, 2026)
This study aimed to analyze the relationship between the duration of gadget use and the incidence of myopia among university students. Methods: This research employed a quantitative approach with a cross-sectional design. The study population consisted of university students, and respondents were selected using a purposive sampling technique. Data on gadget use duration were collected using a structured questionnaire, while myopia status was determined through visual examination and refractive assessment. The collected data were analyzed using appropriate statistical tests to determine the relationship between the duration of gadget use and the incidence of myopia at a significance level of 5%. Results and Discussion: The findings demonstrated a significant relationship between the duration of gadget use and the incidence of myopia among university students. Respondents with longer daily gadget use were more likely to experience myopia than those with shorter durations of use. Prolonged exposure to near-work activities through digital devices is considered to increase accommodative demand and visual stress, which may contribute to the development and progression of myopia. These findings support previous evidence indicating that excessive digital device use is an important environmental risk factor for myopia in young adults. Conclusion: The duration of gadget use is significantly associated with the incidence of myopia among university students. Promoting healthy digital device use, limiting prolonged screen exposure, and encouraging regular visual breaks are recommended to reduce the risk of myopia and maintain visual health among students.